Fisherwomen’s Indigenous and local knowledge - the hidden gems for the management of marine and freshwater resources in Fiji - Kitolelei, Salanieta; Breckwoldt, Annette; Kitolelei, Jokim; Makhoul, Natalie (Frontiers in Marine Science, 2022)
Fisherwomen in Fiji play a vital role in the daily sustenance of their families and they use their Indigenous and local knowledge to harvest resources. Marine and freshwater resources harvested by fisherwomen contribute to the primary protein intake of their families, particularly for those who have limited or no access to other animal products or plant proteins. Over a span of three decades, Fiji experienced an influx in the documentation of women’s contribution and need for fisherwomen's recognition in the fisheries sector; in areas of cultural and/or socio-economic, resource management and decision-making processes. This study examines the Indigenous and local knowledge which fisherwomen utilize to identify their targeted marine and freshwater resources and gauge the population health of their resources. Furthermore, fisherwomen’s perceptions on the conservation status of their resources is used to provide the basis for improved management of culturally, economically and ecologically valuable species. The results of this study compiles Indigenous taxonomic classifications and associated species knowledge which fisherwomen from 11 communities use to help them in identifying and capturing resources. Moreover, the fishing methods, ecological knowledge and perceptions on environmental changes over thirty years provides temporal background on the fisherwomen’s knowledge. The results address knowledge gap between fisherwomen's Indigenous and local knowledge and science by marrying the well-developed knowledge systems. Finally, this study provides recommendations on how the Indigenous and local knowledge of women can contribute to practical and efficient resource management for localized challenges in Fiji.